Kernwapens doden, ook zonder oorlog - Sölle, Dorothee, 1929-2003; Schippers, Aart (Baarn : Ten Have, 1982)
The famous German theology professor and writer as a peace activist: her recent speeches and articles on militarism, armament and the need for a better peace than nuclear arms can produce. On peace organization, especially in the USA. On Hiroshima, the third world, Auschwitz.